Soybean: action of Ac. Fulvic and biostimulants on abiotic stress conditions and primary components of performance (Semiárida, 2020)
The expansion of the cultivation of soybean (Glycine max) in our country was the result of frequent exposure to different environmental conditions in terms of precipitation, radiation and temperature. While today there are regions where there is a gap between the potential yield and the weighted average. The Pampean semiarid Region represents a tangible example due to high temperatures and drought on the soybean crop. The implementation of various technologies today allows you to mitigate the adverse effects of abiotic stress in the cultivation. The objective of the study was to analyze the effects on stress generating applications in seed and leaf Ac. Fulvicos and biostimulants based plant extracts, and the impact on performance and the quality of grain compared with an absolute control under the same conditions. It was used to cultivate DM 4800 GM 4.5 indeterminate. The trial consisted of two blocks with 8 treatments each. In one of the blocks the seed was treated with Biozyme TS, while in the other bloc seed had only commercial treatment. The used bio-stimulants were Biozyme TS, Biozyme TF, Biotron, Raizal, K-Fol and KTionic. Action fitotonic on the metabolic processes of the seed and plant. The variables analyzed were speed of emergency and density, biomass, and expansion of root, aboveground biomass, photosynthesis, interception, height, knots/plant, pods/plant, incidence of Septoria, defoliation, seed number, and thousand-seed weight. It was found that the biostimulants promoted positive differential in these variables. The best results were obtained in the treatments with combined application of biostimulants during the crop cycle.Director: Bardella, Eduardo José
Keywords: Soybean; Biostimulants; Stress; Yield; Quality